Rancang Bangun Sistem Informasi Asistensi ORACLE Berbasis Web Di Prodi Sistem Informasi UNIKOM - effendi, diana; noviansyah, berry (STKIP PGRI Tulungagung, 2016)
Learning process in the Computer Laboratory cannot be separated by quantity and computer specs as well as qualified lecturer. learning process in the Oracle Laboratory of Information System Major can not be held optimally, because many students in the laboratory and limitedÂ time for study. Not all students can be accommodate to solve their problems in the laboratory. This problem is solved with the chosen laboratory assistant. During the process of selecting a laboratory assistant do with conventional process. The election process can not produce a qualified assistant. Besides that,Â scheduling lab assistants performed manually, resulting in a scheduling conflict with class schedules the assistant and needs to create a schedule andÂ printing BAP (Berita Acara Perkuliahan) returned.The certificate of assistance is granted at the end of the semester, done manually and can be made repeatedly. Therefore, need to be built Laboratory Information System Assistance Oracle (SIASLORA) that can process data assistant candidate selection, scheduling assistance Oracle lab, printing BAP (Berita Acara Perkuliahan) and printing aÂ certificate of assistance quickly and accurately. Development method of SIASLORA using prototype development system and structured system approach using context diagram and data flow diagram. The Programing language using PHP (Hypertext Preprocessor) and data base management system (DBMS) using MySQL. With SIASLORA expected to overcome the problems described earlier.Keywords â?? laboratory Oracle, kcomputerize, information system, SIASLORA.